1996
DOI: 10.1111/j.1365-2044.1996.tb15042.x
|View full text |Cite
|
Sign up to set email alerts
|

Intra‐ocular pressure changes during gynaecological laparoscopy

Abstract: Summary

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 11 publications
3
14
0
Order By: Relevance
“…They found that IOP was significantly below the baseline value and never exceeded the pre-induction value. [91011]…”
Section: Discussionmentioning
confidence: 99%
“…They found that IOP was significantly below the baseline value and never exceeded the pre-induction value. [91011]…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, an increased intraperitoneal pressure of 15 mmHg under GA did not adversely affect IOP in women with no preexisting eye disease because the decrease in IOP caused by GA compensated for the increase in IOP caused by the head-down position [7]. Conversely, in rabbits with ␣-chymotrypsin-induced glaucoma in one eye, IOP of both glaucomatous and control eyes increased significantly when an increased intraperitoneal pressure of Յ15 mmHg was combined with the headdown position [8].…”
Section: Discussionmentioning
confidence: 99%
“…Lentschener et al 21 . found that IOP decreased significantly after induction of anaesthesia, remained unchanged after pneumoperitoneum had been established and increased with head‐down position but did not significantly change.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 Therefore, concern may be raised that laparoscopic surgery could contribute to early intraoperative aggravation of pre-existing eye disease in a certain subset of patients. 6 In the present study, we investigated IOP at each step of gynaecological laparoscopy carried out under general anaesthesia.…”
Section: Introductionmentioning
confidence: 99%